Screw loose, stuck screw - Honda, Lilian (Revista Desassossego, 2021)
Psychological sufferings are recurrent themes in Adília Lopes' poetry, whether in a markedly critical or ironic, if not pure invective, record against psychiatry and psychoanalysis professionals, or in the allusion to psychotropic drugs, their adverse effects on the organism and carelessness with which they are prescribed. Based on the philosophical reflection found in Georges Canguilhem’s The Normal and the Pathological, in which the paradigms that structured medical-scientific knowledge and the notions of health/disease, normality/pathology and anomaly are investigated, concepts that started to form the basis for the multiplication of regulatory devices in all spheres of social life, the multiple meanings of this game involving compliance with the rules and psychic suffering in Adília Lopes' poetics made it necessary to look for a more precise conceptualization of “normality” and “abnormality”.